Use of Consumer Wearables in Health Research: Issues and Considerations - Rosie Dobson; Melanie Stowell; Jim Warren; Taria Tane; Lin Ni; Yulong Gu; Judith McCool; Robyn Whittaker (Journal of Medical Internet Research, 2023)
As wearable devices, which allow individuals to track and self-manage their health, become more ubiquitous, the opportunities are growing for researchers to use these sensors within interventions and for data collection. They offer access to data that are captured continuously, passively, and pragmatically with minimal user burden, providing huge advantages for health research. However, the growth in their use must be coupled with consideration of their potential limitations, in particular, digital inclusion, data availability, privacy, ethics of third-party involvement, data quality, and potential for adverse consequences. In this paper, we discuss these issues and strategies used to prevent or mitigate them and recommendations for researchers using wearables as part of interventions or for data collection.